Capillary Blood Self‐Sampling for Therapeutic Drug Monitoring: A Mixed‐Methods Usability Study of the True Dose® Kit. - Crafoord, Marie-Therése; Hedayati, Elham; Johnsson, Aina; Banerjee, Baisakhi (BioMed Research International, 2025)
Objective: This study evaluates the usability in accordance with EN 62366 of the True Dose kit for capillary blood self‐sampling, to be used to analyze, specify, design, verify, and validate usability as it relates to the safety of medical devices focusing on user performance, experience, and user confidence through a mixed‐methods approach. The usability engineering process is needed to fulfill user interface design requirements as part of product development at True Dose kit. Methods: The study employed a convergent parallel design, integrating quantitative and qualitative data. Twenty‐five participants, recruited through convenience sampling, used the True Dose kit to perform capillary blood self‐sampling. Quantitative data were collected using three key performance metrics—collection of sufficient blood volume, absence of air bubbles, and duration of the self‐sampling process—along with two questionnaires, the System Usability Scale (SUS) and the Test Feedback Questionnaire (TFQ), to comprehensively assess user performance and experience. In contrast, qualitative data were obtained from interviews and free‐text responses. The integration of findings highlighted areas of convergence and divergence between the quantitative and qualitative data. Results: The overall SUS score was 82.70, indicating high usability. However, participants reported challenges with the complexity of instructions and stress associated with blood flow management. Qualitative insights revealed a preference for simplified visual guidance and highlighted the need for precise feedback mechanisms to ensure the correct execution of sampling steps. Despite these challenges, 92% of participants collected the required blood sample, with a median self‐sampling duration of 10.42 min. Conclusion: The True Dose kit demonstrates high usability potential, but improvements in instructional design and stress management are needed to enhance user experience and ensure consistent performance. Trial Registration: EUCT Number: 2024‐514818‐12‐00